Mathematical concepts and skills needed for stoichiometric calculations in general chemistry - Belisario, Belinda Velayo (1979)
This study attempted to identify mathematical concepts and skills that are needed for stoichiometric calculations in General Chemistry. The respondents of the study were 62 teachers of General Chemistry course in ten different colleges and universities in Metro Manila, who have been teaching the subject for more than one year. A questionnaire was used as a research instrument. The findings of the study revealed that the mathematical skills that are often needed for stoichiometric calculations in General Chemistry are solving problems on ratio and proportion, familiarity with the general units and interrelation of the metric system, multiplication and division of numbers with exponents and on writing of numbers in scientific notation.
Vita.
Thesis (M.A. Chemistry Education)--University of the Philippines, Diliman.
Keywords: Chemistry -- Study and teaching (Higher) -- Philippines -- Manila Metropolitan Area; Chemistry teachers -- Philippines -- Manila Metropolitan Area; Chemistry -- Problems, exercises, etc